2017
DOI: 10.1016/j.ebiom.2017.03.029
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil to Lymphocyte Ratio is Associated With Outcome During Ipilimumab Treatment

Abstract: BackgroundIpilimumab (IPI) and BRAF inhibitors (BRAFi) improve survival in melanoma, but not all patients will benefit and toxicity can be significant. Pretreatment neutrophil to lymphocyte ratio (NLR) has been associated with outcome in IPI-treated patients, but has not been studied during treatment or in BRAFi-treated patients.MethodsUsing a prospectively maintained database, patients with unresectable stage III or IV melanoma treated with IPI or a BRAFi (vemurafenib or dabrafenib as monotherapy) from 2006 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
79
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(88 citation statements)
references
References 36 publications
6
79
3
Order By: Relevance
“…It is consequently favorable to have more LYMs relative to neutrophils (i.e., a low NLR). Relationships between NLR and OS have been reported previously across both tumor‐types and checkpoint inhibitors . NLR provided nearly as good improvement as LYM in the AAD model (1.7 × 10 −4 vs. 1.0 × 10 −4 ; Table ) and could consequently have been exchanged to NLR with only minor worsening of the model fit.…”
Section: Discussionsupporting
confidence: 58%
“…It is consequently favorable to have more LYMs relative to neutrophils (i.e., a low NLR). Relationships between NLR and OS have been reported previously across both tumor‐types and checkpoint inhibitors . NLR provided nearly as good improvement as LYM in the AAD model (1.7 × 10 −4 vs. 1.0 × 10 −4 ; Table ) and could consequently have been exchanged to NLR with only minor worsening of the model fit.…”
Section: Discussionsupporting
confidence: 58%
“…Our findings may help explain the biologic relationship between the NLR and prognosis in patients with cancer. The prognostic significance of an elevated NLR is observed with remarkable consistency across many cancer types and stages of disease . What remains unclear is whether NLR elevation represents a reaction to immunosuppressive factors from the tumor or, alternatively, reflects an intrinsic host variable (ie, dysfunctional immune response) that leads to a more aggressive clinical course.…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic significance of this immune‐based marker is particularly interesting in light of the clinical success of immunotherapy in melanoma. Recent studies have demonstrated that an elevated baseline NLR is prognostic for worse overall survival (OS) and progression‐free survival (PFS) before checkpoint inhibitor therapy with CTLA‐4 and/or PD‐1 blockade . Although the prognostic value of the NLR is clear, how this translates into clinical utility remains undefined.…”
Section: Introductionmentioning
confidence: 99%
“…and Di Giacomo et al . indicated no significant association between pretreatment NLR level but an association with post‐treatment NRL level, while Cassidy et al . evaluated the changes in the NLR after ICI treatment.…”
Section: Discussionmentioning
confidence: 99%